Australian employment services: Help or hindrance in the achievement of mutual obligation?. Issue 4 (6th November 2019) - O'Halloran, David; Farnworth, Louise; Thomacos, Nikos
Abstract: The concept of mutual obligation underpins Australian employment services. In return for receiving income support, there are three elements of mutual obligation: to actively seek work; to improve one's competitiveness in the labour market; and to contribute to the community. Failing to undertake mutual obligation activities results in sanctions, usually unemployment benefit suspension or cancellation. In the year 2017/18, one mutual obligation activity, compulsory employment service provider appointments, accounted for more than 93 per cent of sanctions. The study reported here explores unemployed and recently employed workers' experiences of appointments and their attitudes to the concept of mutual obligation. The findings are that unemployed workers say appointments have little utility for advancing elements of mutual obligation and are psychologically harmful. Non‐attendance may be a form of self‐protection although seeking a medical exemption or dropping out of the system altogether also appears to be a common self‐protection strategy. We also find that non‐attendance at appointments cannot be conflated with a negative attitude to mutual obligation and that unemployed workers want services that are effective and psychologically positive to help them to fulfil their mutual obligations.